Freeform optics for LED packages and applications - Wang, Kai; Liu, Sheng; Luo, Xiaobing, 1974-; Wu, Dan (Hoboken, NJ : Wiley, 2017)
A practical introduction to state-of-the-art freeform optics design for LED packages and applications By affording designers the freedom to create complex, aspherical optical surfaces with minimal or no aberrations, freeform design transcends the constraints imposed by hundreds of years of optics design and fabrication. Combining unprecedented design freedom with precise light irradiation control, freeform optics design is also revolutionizing the design and manufacture of high quality LED lighting. The first and only book of its kind, Freeform Optics for LED Packages and Applications helps put readers at the forefront of the freeform optics revolution. Designed to function as both an authoritative review of the current state of the industry and a practical introduction to advanced optical design for LED lighting, this book makes learning and mastering freeform optics skills simpler and easier than ever before with: -Real-world examples and case studies systematically describing an array of algorithms and designs-from new freeform algorithms to design methods to advanced optical designs -Coding for all freeform optics algorithms covered-makes it easier and more convenient to start developing points of freeform optics and construct lenses or reflectors, right away -Case studies of a range of products, including designs for a freeform optics LED bulb, an LED spotlight, LED street lights, an LED BLU, and many more Freeform Optics for LED Packages and Applications is must-reading for optical design engineers and LED researchers, as well as advanced-level students with an interest in LED lighting. It is also an indispensable working resource design practitioners within the LED lighting industry.
Front Matter -- Introduction -- Review of Main Algorithms of Freeform Optics for LED Lighting -- Basic Algorithms of Freeform Optics for LED Lighting -- Application-Specific LED Package Integrated with a Freeform Lens -- Freeform Optics for LED Indoor Lighting -- Freeform Optics for LED Road Lighting -- Freeform Optics for a Direct-Lit LED Backlighting Unit -- Freeform Optics for LED Automotive Headlamps -- Freeform Optics for Emerging LED Applications -- Freeform Optics for LED Lighting with High Spatial Color Uniformity -- Codes of Basic Algorithms of Freeform Optics for LED Lighting.
Includes bibliographical references and index.
Online resource; title from PDF title page (John Wiley, viewed August 28, 2017).
Keywords: LED lighting; TECHNOLOGY & ENGINEERING / Mechanical; LED lighting; Electronic books